STATE SYSTEM OF HOSPITALITY AND TOURISM SUPPORT IN THE CRISIS - Khudaverdiyeva, V. (Municipal economy of cities. Series: «Economy science», 2022)
The urgency of this problem, its practical significance determined the choice of research topic and served as a basis for formulating its goals and objectives. The purpose of research work is to conduct a comprehensive analysis of measures to support tourism in modern conditions in the context of world and domestic experience. Achieving this goal requires the solution of the following tasks: to assess the main problem areas of tourism in a crisis; to systematize the world and domestic experience of supporting the sphere of tourism in the current conditions; assess possible scenarios for the recovery of tourism, taking into account the measures taken and current trends. The article identifies the importance of hospitality and tourism, which is a vital source of income from tourism and foreign direct investment, as well as jobs, especially for women and youth. The closure in March 2019 of the boundaries of external and internal, not only the revenues of tourism companies to zero, but also led in some cases to significant losses. Many companies in the country are facing the threat of bankruptcy of hotels, transport, as well as services, excursions and consulting services in the field of tourism. The following technical assistance activities in the field of institutional strengthening and resilience need to be identified that can help Member States to guide and support recovery processes from the negative effects of COVID-19, in particular to support job retention in the tourism sector: adaptations during COVID-19; public-private partnership to improve tourism; development of communication strategy for crisis response; media trainings for enterprises serving the tourism sector; capacity building programs in the field of tourism development and management in order to accelerate recovery; strategy of national development of human capital in the field of tourism; development and strengthening of target management organizations; strengthening the potential of domestic tourism, development and promotion of local tourism products; - realization of women's rights and material opportunities through tourism; youth employment project in the field of tourism; introduction of information and communication and technical innovations.